2020
DOI: 10.1371/journal.pone.0234123
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy and safety of drug interventions for primary and secondary prevention of osteoporotic fractures in postmenopausal women: Network meta-analysis followed by factor and cluster analysis

Abstract: We aimed to evaluate the comparative efficacy and safety of drugs respectively for primary prevention and secondary prevention of osteoporotic fractures in postmenopausal women (PMW), and to further identify the optimal intervention(s) respectively for the two groups when efficacy and safety both considered. We searched three databases. Bayesian network meta-analyses were conducted for two efficacy outcomes (vertebral fractures and nonvertebral fractures) and two safety outcomes (tolerability and acceptability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 63 publications
1
12
0
Order By: Relevance
“…This is further complicated by the limited evidence for falls prevention in patients with cognitive impairment [25]. In contrast, there is consistent evidence for the effectiveness of AOMs in patients with high fracture risk [26], post hip fracture [27] and with cognitive impairment [28]. The challenges for effective secondary fracture prevention using AOMs occur at the system, pharmacological, and patient level [9,29].…”
Section: Discussionmentioning
confidence: 99%
“…This is further complicated by the limited evidence for falls prevention in patients with cognitive impairment [25]. In contrast, there is consistent evidence for the effectiveness of AOMs in patients with high fracture risk [26], post hip fracture [27] and with cognitive impairment [28]. The challenges for effective secondary fracture prevention using AOMs occur at the system, pharmacological, and patient level [9,29].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent meta-analysis including only randomized controlled trials comparing different drugs for the management of postmenopausal osteoporosis, romosozumab depicted the lowest rate of new vertebral fractures [ 94 ]. A sophisticated network meta-analysis reported that while romosozumab, teriparatide, denosumab, and risedronate are the optimal treatments for secondary prevention of osteoporotic fractures in the setting of postmenopausal osteoporosis, only zoledronate has been shown to significantly reduce both vertebral and non-vertebral fractures for primary prevention in this setting [ 95 ]. Conversely, Ding and colleagues stratified various osteoporosis drugs in postmenopausal women either with or without prevalent vertebral fracture and observed that romosozumab was the only drug that could reduce clinical and vertebral fractures in both populations [ 96 ].…”
Section: Monoclonal Antibodies Against Sclerostin In Human Osteopomentioning
confidence: 99%
“…Mariscal et al performed a meta-analysis in men and women treated with romosozumab and described that adverse effects of romosozumab were comparable to placebo, except for an increased risk of adverse reactions at the injection site [ 104 ]. An extensive network meta-analysis on primary and secondary prevention of osteoporotic fractures demonstrated a tolerability and acceptability similar between romosozumab, teriparatide, and denosumab compared to placebo [ 95 ]. In summary, romosozumab appears to be a safe and well-tolerated drug.…”
Section: Safety Profile Of Romosozumabmentioning
confidence: 99%
“…The second meta-analysis was a more thorough analysis of all medications used to treat osteoporosis and focused on effects on primary and secondary prevention. 19 The analysis concluded that romosozumab reduced the risk of vertebral (RR = 0.30; 95% CI = 0.23-0.41) and nonvertebral (HR = 0.69; 95% CI = 0.56-0.84) fractures compared with placebo in secondary fracture prevention. It also suggested that romosozumab was superior to alendronate, bazedoxifene, raloxifene, risedronate, and strontium in reduction of vertebral fractures and superior to bazedoxifene and raloxifene in reduction of nonvertebral fractures.…”
Section: Clinical Efficacymentioning
confidence: 99%